(untitled) (Texas Journal of Medical Science, 2023)
Lung cancer remains a significant global health concern, characterized by uncontrolled cell proliferation and metastatic potential. This study delves into the intricate the correlation between oxidative stress and lung cancer., as well as the potential of paclitaxel as a treatment option. We explore the enzymatic activity of GST, CAT, and MDA in lung cancer patients and a control group, considering their smoking status. Additionally, we investigate the impact of paclitaxel on reactive oxygen species (ROS) production in a malignant cell line. The results demonstrate significant variations in enzymatic activity and ROS induction in lung cancer patients, emphasizing the importance of these factors in the disease’s progression. The findings shed light on the potential of paclitaxel as an agent for ROS modulation in lung cancer therapy, providing valuable insights for improved treatment strategies and enhanced patient outcomes